Pemeriksaan Perdamaian dalam Arbitrase: Dasar Putusan Arbitrase untuk Menjamin Keadilan - Olivia Tiara Dewi; Mirna Nirmala Sari Harahap (Journal of Legal, Political, and Humanistic Inquiry, 2026)
Arbitration is designed as an alternative dispute resolution mechanism that emphasizes efficiency, finality, and party autonomy. Nevertheless, the pursuit of justice within arbitration requires procedural safeguards that ensure fairness and balance between the disputing parties. One essential aspect in this regard is the examination of settlement during arbitral proceedings. This study analyzes the role of settlement examination as the legal basis of arbitral awards in guaranteeing justice, viewed through the perspective of Indonesian arbitration law. Using a normative legal research method, this paper examines statutory regulations, legal doctrines, and relevant scholarly opinions concerning arbitration and settlement mechanisms. The findings indicate that settlement examination strengthens substantive and procedural justice by providing space for dialogue, preventing inequality of bargaining positions, and enhancing voluntary compliance with arbitral awards. Moreover, arbitral awards that consider settlement aspects demonstrate stronger legitimacy and lower risks of annulment or enforcement disputes. The study concludes that settlement examination does not diminish the final and binding nature of arbitral awards, but rather enhances their quality and credibility. Accordingly, the integration of settlement examination should be regarded as a fundamental element in realizing just and effective arbitration.